Peningkatan Nilai Ekonomi Material PVC Lembaran Dari Sampah Sisa Bahan Baku di Industri Alas Kaki - Afrazilulla Anyankani Qorira; Mohamad Arif Waskito (Jurnal Desain Indonesia., 2020)
Garbage is a part of people's lives. Especially plastic waste that continues to accumulate and also endangers environmental life, especially waste generated by an industry. Especially PVC plastic waste in the Footwear Industry. The amount of plastic waste is waste and the decomposition of plastic waste takes a very long time. To overcome these problems, it is necessary to carry out activities that make plastic waste can be reused properly. Using the experimental method can provide some new ideas and opportunities, in utilizing PVC plastic waste in the footwear industry. This can give rise to several new things and ideas such as designing a women's footwear with plastic waste of the type Mica Plastik (PVC) which is relatively rarely applied to functional products. The benefits of research activities on people's lives are creating new job opportunities and new businesses.